Minimizing electrostatic interactions from piezoresponse force microscopy via capacitive excitation. Issue 1 (January 2020) - Zhu, Qingfeng; Esfahani, Ehsan Nasr; Xie, Shuhong; Li, Jiangyu
HIGHLIGHTS: Capacitive excitation piezoresponse force microscopy (PFM) is developed to minimize electrostatic interactions. The piezoresponse measured by capacitive excitation PFM (ce-PFM) is smaller than conventional PFM. The domain contrast obtained by ce-PFM is sharper than conventional PFM. Abstract: Piezoresponse force microscopy (PFM) has emerged as one of the most powerful techniques to probe ferroelectric materials at the nanoscale, yet it has been increasingly recognized that piezoresponse measured by PFM is often influenced by electrostatic interactions. In this letter, we report a capacitive excitation PFM (ce-PFM) to minimize the electrostatic interactions. The effectiveness of ce-PFM in minimizing electrostatic interactions is demonstrated by comparing the piezoresponse and the effective piezoelectric coefficient measured by ce-PFM and conventional PFM. The effectiveness is further confirmed through the ferroelectric domain pattern imaged via ce-PFM and conventional PFM in vertical modes, with the corresponding domain contrast obtained by ce-PFM is sharper than conventional PFM. These results demonstrate ce-PFM as an effective tool to minimize the interference from electrostatic interactions and to image ferroelectric domain pattern, and it can be easily implemented in conventional atomic force microscope (AFM) setup to probe true piezoelectricity at the nanoscale.